Introduction (The Toro Historical Review, 2025)
Welcome to volume 16, issue 2 of The Toro Historical Review! This issue features three essays produced in upper-division history classes and represents a remarkable achievement in undergraduate research, writing, and editing. Well done all! Congratulations to the authors: Mansur Abdullah Wilfred Navarrete Quinto Christian Villanueva And a special thank you to our editorial team, which has worked hard to bring this issue to fruition. Thank you!